Assessing the potential of surplus clean power in reducing GHG emissions in the building sector using game theory; a case study of Ontario, Canada. Issue 3 (6th August 2019) - Haghi, Ehsan; Kong, Qinghao; Fowler, Michael; Raahemifar, Kaamran; Qadrdan, Meysam
Abstract : This work assesses the potential of surplus electricity in reducing greenhouse gas (GHG) emissions in the building sector. The assessment is done by modelling the interaction of government and energy consumer using game theory. The government can provide discounted power to energy consumer by covering a fraction of the off‐peak price to encourage the replacement of natural gas consumption with electricity. This replacement reduces GHG emissions from the building sector. Energy consumer adopts electricity‐based technologies only if it leads to a lower heat and electricity supply cost. Cost‐effectiveness of solid oxide fuel cell, air–source heat pump (ASHP), and battery and hydrogen storage are assessed as alternatives to natural gas combined heat and power (CHP) and boiler technologies. The modelling results show that ASHP is the only technology that can compete with natural gas CHP and boiler. ASHP is chosen by the energy consumer when discounts of 4.5 cents/kWh or more for off‐peak electricity are available. The analysis also showed that CHP could be completely replaced by grid power at discount value of 4.5 cents/kWh and up. Natural gas boilers continue playing a role in building heating supply even under increased discount for off‐peak electricity price.